"Australia is one of the darkest markets in the world": the global importance of Australian tobacco control. (26th November 2003) - Chapman, S; Byrne, F; Carter, S M
Abstract : "Australia is one of the darkest markets in the world... it probably is the darkest, I mean ourselves and Canada fight every month for who's got the darkest conditions to do tobacco manufacturing and marketing. And one of the things we can offer the world is what we do best, which is how to work, maximize, proactively drive our market position in a market that's completely dark. Now that takes a different skillset... a different type of learning. We need to export that... we know we have a lot of expatriates who come down to Australia for learning... they can come here and learn these techniques and take them back to Europe or Latin America or to the United States or to Africa... But the other thing that is really good for us is that we are also a huge net exporter of Australian talent... about 30 or 40 people currently off-shore... We do things really differently here than most other BAT organizations." David Crowe, Marketing Director, British American Tobacco (BAT) Australia 1